Do Clean Hands ensure healthy growth? Theory and practice in the battle against corruption - Raffaella Coppier; Mauro Costantini; Gustavo Piga (Institute for Advanced Studies (IHS), 2009)
This paper analyzes the existing relationship between economic growth and the monitoring of corruption and examines the possible outcome of the implementation of a State reform in order to weed out corruption. Growth is always higher when monitoring is high and therefore corruption eradicated. But growth declines when monitoring against corruption is not too high, say intermediate, so much that it makes an equilibrium with corruption and little monitoring a more growth-enhancing solution. It is also stressed that when reforms to combat corruption appear to be implausible, they tend to curb most productive investments. The model is estimated using a dynamic panel data approach for Italy. Italy has been plagued by corruption and in the late 80s and early 90s several scandals erupted which led to the well-known Clean Hands (Mani pulite) inquiries. Empirical results support the theoretical model.
Keywords: C33; D73; K42; 330; corruption; growth; reform; panel data; Wirtschaftswachstum; Korruption; Kriminalpolitik; Makroökonomischer Einfluss; Italien